Transformative Leadership of Tuan Guru Kiai Haji Muhammad Zainuddin Abdul Madjid in Developing Modernization of Islamic Education at Nahdlatul Wathan Pancor Islamic Boarding School East Lombok, West Nusa Tenggara - Moh. Hifzul Muiz; Priatna , Tedi; Erihadiana, Mohamad; Hidayat , Asep Achmad (IJGIE (International Journal of Graduate of Islamic Education), 2024)
The background of this study is that in the current era of globalization, there are Islamic boarding schools that have not been able to adapt to the development of the times, resulting in the Islamic boarding school not being able to develop the modernization of Islamic education and not being able to develop in a better direction. However, there are also Islamic boarding schools that are able to adapt to all forms of development that occur, such as the Nahdlatul Wathan Pancor Islamic boarding school in East Lombok, West Nusa Tenggara. The Islamic boarding school was founded during the colonial era by a charismatic kiai, a national hero, namely Tuan Guru Kiai Haji Muhammad Zainuddin Abdul Madjid. The Islamic boarding school has grown rapidly and still exists today. This is due to the transformative leadership model of its kiai as a top leader. The transformative leadership of the kiai himself has provided a lot of inspiration for the progress of Islamic educational institutions, because in his leadership he has his own uniqueness and characteristics. This study aims to find out how the transformative leadership model of the founder of the Nahdlatul Wathan Pancor Islamic boarding school in East Lombok, West Nusa Tenggara, develops the modernization of Islamic education, the implementation of his leadership and the results of his leadership. The method used in this study is descriptive-analytical with a phenomenological approach. Meanwhile, in drawing conclusions, this study applies an inductive method, namely using general data, then making specific conclusions. The results of this study found that in the era of Tuan Guru Kiai Haji Muhammad Zainuddin Abdul Madjid's leadership, many transformations and modernizations have been carried out, such as organizing Islamic religious education and teaching with a madrasa system in addition to maintaining the sorogan system, opening public schools in addition to madrasas in the West Nusa Tenggara region, integrating religious knowledge and general knowledge, implementing multicultural education in West Nusa Tenggara, initiating and driving higher education, and implementing multicultural education.